1980
DOI: 10.1073/pnas.77.1.423
|View full text |Cite
|
Sign up to set email alerts
|

A selective inhibitor of cell proliferation from normal serum.

Abstract: A factor in normal serum that selectively and reversibly inhibits proliferation of cells in culture has been enriched 160-fold from calf serum by sequential ammonium sulfate precipitation, gel filtration, and lectin-affinity chromatography. DNA synthesis of normal (but not transformed) rat hepatocytes, human lymphoblast lines, and mitogen-stimulated murine spleen cells is inhibited by >90%, and Vero, murine myeloma, MELC, and a human colon carcinoma cell line to a lesser extent. Growth of other cell lines test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…Serum contains proteins, polypeptides, hormones, metabolites, nutrients and minerals. In addition, serum may also contain substances inhibiting cell proliferation (Harrington and Godman 1980) and, for this reason, serum is heat-treated, a process that removes complement from the serum and reduces the cytotoxic action of immunoglobulins without damaging polypeptide growth factors. This may explain why heat-treated AHS produced a greater growth response than untreated AHS.…”
Section: Discussionmentioning
confidence: 99%
“…Serum contains proteins, polypeptides, hormones, metabolites, nutrients and minerals. In addition, serum may also contain substances inhibiting cell proliferation (Harrington and Godman 1980) and, for this reason, serum is heat-treated, a process that removes complement from the serum and reduces the cytotoxic action of immunoglobulins without damaging polypeptide growth factors. This may explain why heat-treated AHS produced a greater growth response than untreated AHS.…”
Section: Discussionmentioning
confidence: 99%
“…We have partially purified (around 1,000-fold) an inhibitory factor of neuroblast proliferation from FCS. Other au thors [6] have identified an inhibitory factor from calf serum which inhibits proliferation of several cell types in culture. This factor was only purified by ammonium sulfate pre cipitation and gel filtration: its molecular weight was found to be about 200,000 from its position in the elution profile from Ultrogel AcA 34.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, sera also contain inhibitors of growth [9]. Recently, Harrington and Goldman [6] showed that proliferative activity of normal cells was reduced as the concentration of se rum in the medium was increased. These au thors have identified an inhibitory serum fraction that suppresses the multiplication of certain types of cells, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…McMahon et al [29] have purified an inhibitor of cell proliferation from rat liver, which inhibits only normal rat liver cells but not rat liver tumor cells. Other growth inhibitors have been detected in non-neural cells [30], in calf serum [31], in human plasma-derived serum [32], in rat ascites [33], and in NIH/3T3 cells. Recently in human platelets distinct from the platelet-derived TGF-(3, an EGI was demonstrated, which significantly inhibited the growth of nonmalignant cell lines in monolayer cultures [34].…”
Section: Discussionmentioning
confidence: 99%